Analysis of Difficulty Understanding Student Mathematica by Using Online Learning Model - ., Fitriani; Umar, Kholid; Pasaribu, F; Novitasari, Wiwik; Sofyan Samosir, Beni; ., Yusmiati (KnE Social Sciences, 2023)
This research is based on the low understanding of students’ mathematics. One of the causes for the low understanding of students’ mathematics is a factor in the students themselves in the form of student difficulties in solving problems related to the material in the Differential Calculus course. The purpose of this study was to describe the difficulties of students’ mathematical understanding in solving problems in the Differential Calculus Course using the online learning model. This type of research uses a qualitative approach and is descriptive in nature. The subjects of this study were first semester students taking Differential Calculus courses in the Mathematics Education study program, Muhammadiyah University of Tapanuli Selatan, Academic Year 2020/2021. The instrument used in this study was an interview. The results showed that the difficulties of students’ mathematical understanding in solving problems in the Differential Calculus course using the online learning model were related to technical difficulties, adaptation difficulties and internal difficulties for each individual student. To overcome these difficulties, it is necessary to have a more varied strategy for using online learning media. Keywords: Online learning; mathematic; media